Evapotranspiration from a satellite-based surface energy balance for the Snake Plain Aquifer in Idaho - Allen, Richard G., author; Morse, Anthony, author; Tasumi, Masahiro, author; Trezza, Ricardo, author; Bastiaanssen, Wim, author; Wright, James L., author; Kramber, William, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2002)
SEBAL (Surface Energy Balance Algorithm for Land) is an image-processing model comprised of 25 submodels for calculating evapotranspiration (ET) as a residual of the surface energy balance. SEBAL was developed in the Netherlands by Bastiaanssen and has been modified during Idaho studies for application to irrigated agriculture, rangeland, mountainous terrain and clear, cold lakes under semiarid conditions. SEBAL has been applied in many developing countries and has now been applied in southern Idaho to predict monthly and seasonal ET for water rights accounting and for operation of ground water models. Results from SEBAL have been compared and validated using precision-weighing lysimeter measurements from the U.S. Department of Agriculture - Agricultural Research Service (USDA-ARS) at Kimberly, Idaho, and from Utah State University for the Bear River. ET for periods between satellite overpasses was computed using ratios of ET from SEBAL to reference ET computed for ground-based weather stations. ET maps via SEBAL provide the means to quantify, in terms of both the amount and spatial distribution, ET from individual fields. The ET images generated by SEBAL show a progression of ET during the year as well as distribution in space. Initial application and testing of SEBAL indicates substantial promise as an efficient, accurate, and relatively inexpensive procedure to predict the actual evaporation fluxes from irrigated lands throughout a growing season. ET from satellite images may replace current procedures used by Idaho Department of Water Resources and other management entities that rely on ground-based ET equations and generalized crop coefficients that have substantial uncertainty.
USCID/EWRI conference
Satellite-based SEBAL
Not digitized by CSUL Digital Services.
Presented at the 2002 USCID/EWRI conference, Energy, climate, environment and water - issues and opportunities for irrigation and drainage on July 9-12 in San Luis Obispo, California.